Amplified Electrochemical Immunosensor for Calmodulin Detection Based on Gold‐Silver‐Graphene Hybrid Nanomaterials and Enhanced Gold Nanorods Labels. Issue 9 (24th July 2014) - Geng, Ping; Fu, Ying; Yang, Meicheng; Sun, Qianqian; Liu, Kai; Zhang, Xinai; Xu, Zhiai; Zhang, Wen
Abstract Calmodulin (CaM) is an important intracellular calcium‐binding protein. It plays a critical role in a variety of biological and biochemical processes. In this paper, a new electrochemical immunosensing protocol for sensitive detection of CaM was developed by using gold‐silver‐graphene (AuAgGP) hybrid nanomaterials as protein immobilization matrices and gold nanorods (GNRs) as enhanced electrochemical labels. Electrode was first modified with thionine‐chitosan film to provide an immobilization support for gold‐silver‐graphene hybrid nanomaterials. The hybrid materials formed an effective matrix for binding of CaM with high density and improved the electrochemical responses as well. Gold nanorods were prepared for the fabrication of enhanced labels (HRP‐Ab2‐GNRs), which provided a large capacity for HRP‐Ab2 immobilization and a facile pathway for electron transfer. With two‐step immunoassay format, the HRP‐Ab2‐GNRs labels were introduced onto the electrode surface, and produced electrochemical responses by catalytic reaction of HRP toward enzyme substrate of hydrogen peroxide (H2O2) in the presence of thionine. The proposed immunosensor showed an excellent analytical performance for the detection of CaM ranging from 50 pg mL−1 to 200 ng mL−1 with a detection limit of 18 pg mL−1. The immunosensor has also been successfully applied to the CaM analysis in two cancer cells (HepG2 and MCF‐7) with high sensitivity, which has shown great potency for improving clinic diagnosis and treatment for cancer study.